Can the Skeletal Muscle Carnosine Response to Beta-Alanine Supplementation Be Optimized? - Perim, Pedro; Marticorena, Felipe Miguel; Ribeiro, Felipe; Barreto, Gabriel; Gobbi, Nathan; Kerksick, Chad; Dolan, Eimear; Saunders, Bryan (Frontiers in Nutrition, 2019)
Carnosine is an abundant histidine-containing dipeptide in human skeletal muscle and formed by beta-alanine and L-histidine. It performs various physiological roles during exercise and has attracted strong interest in recent years with numerous investigations focused on increasing its intramuscular content to optimize its potential ergogenic benefits. Oral beta-alanine ingestion increases muscle carnosine content although large variation in response to supplementation exists and the amount of ingested beta-alanine converted into muscle carnosine appears to be low. Understanding of carnosine and beta-alanine metabolism and the factors that influence muscle carnosine synthesis with supplementation may provide insight into how beta-alanine supplementation may be optimized. Herein we discuss modifiable factors that may further enhance the increase of muscle carnosine in response to beta-alanine supplementation including, (i) dose; (ii) duration; (iii) beta-alanine formulation; (iv) dietary influences; (v) exercise; and (vi) co-supplementation with other substances. The aim of this narrative review is to outline the processes involved in muscle carnosine metabolism, discuss theoretical and mechanistic modifiable factors which may optimize the muscle carnosine response to beta-alanine supplementation and to make recommendations to guide future research.